Manajemen Laba Memoderasi Pengaruh Perubahan Laba, Perubahan Nilai Buku Ekuitas pada Relevansi Nilai Informasi Akuntansi - Andriawan, I Gede Ardian; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2019)
The research objective is to prove earnings management moderates the effect of earnings changes and changes in equity book values on the relevance of the value of accounting information. Data analysis using multiple regression analysis and moderated regression analysis is used to test earnings management in moderating the effect of earnings changes and changes in equity book values on the relevance of the value of accounting information. The results of the study are changes in earnings and changes in the book value of equity have a positive effect on the relevance of the value of accounting information, in addition earnings management weakens the influence of changes in earnings and changes in equity book values on the relevance of accounting information. The research implications are supporting and adding empirical evidence about agency theory, and positive contributions to users of financial statements. Keywords: Value relevance, profit, equity book value, earnings management